Movement Disorders in Childhood Thalamic Tumors - Rebecca Garcia-Sosa; Joanna Blackburn (Pediatric Neurology Briefs Publishers, 2018)
Investigators form St. Jude Children's Research Hospital in Memphis, Tennessee analyzed movement disorder outcomes in patients with childhood thalamic tumors.